Morphometry of Daphnia lumholtzi in Lake Texoma, OK, USA - Beyer, Jessica E; Hambright, K David (In supplement to: Beyer, JE; Hambright, KD (2019): The niche and morphology of the invasive Daphnia lumholtzi in a subtropical reservoir, 20 years after invasion. Journal of Plankton Research, 41(2), 90-100, https://doi.org/10.1093/plankt/fby053, 2019)
In Lake Texoma, OK, USA, we measured the morphometry of Daphnia lumholtzi. Samples were collected at five pelagic sites (see below for coordinates) over the course of fourteen months (June 2010-July 2011). Zooplankton were collected using vertical tow over the full water column (depth-integrated) with a Wisconsin-type net (350-μm mesh, aperture diameter 10.5 cm). Zooplankton were enumerated and morphology of Daphnia lumholtzi was measured using a dissecting microscope.